Model Penilaian Keadilan Terhadap Penanganan Rekonstruksi Rumah Bagi Korban Gempa Bumi Di Bantul - Muhammad Wahyu Kuncoro (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
The purpose of this research was to test the fairness evaluation Judgement models by Tyler (1994) in house reconstructions to the earthquake victims. There are six possibilities of model tested. The research hypothesis was: "The fairness evaluation judgement models by Tyler (1994) matched with the collected data ",The research sampled 181 earthquake victims on 27 May 2006 that are randomly sampled. Data obtained by using6 scales, namely resource scale, control scale, appraisal of interactional justice scale, appraisal of distributive justice scale, appraisal of procedural justice scale and appraisal of justice impact scale. The data analysis that used was SEM and computed by AMOS ver 6.o. The result of this research showed that the model that matched with the collected data was saturated justice model. This model explained that the resource motives and relational motives had well balanced infiuences to appraisal of distributive and procedural justice.